Influence of platinum on structural thick film gas sensor based on lanthanum oxide-doped tin (IV) oxide for carbon dioxide detection - Ehsani, Maryam (2014)
Industrialization in societies has increased the needs of gas sensor technology for natural reservation and cover numerous kinds of toxic gases and chemical compounds. The carbon dioxide gas, one of the primary greenhouse gases in the earth’s atmosphere,which is increasing with the revolution of the industry and human activities such as combustion of fossil fuels and deforestation. Although carbon dioxide gas is one of the odorless greenhouse gases, it is harmful for animal life and human health in high concentration. Different kinds of detectors are used to detect the carbon dioxide gas, but the have disadvantages such as high cost, needs of maintenance and regular overhaul. There are different types of solid-state gas sensors, with several fabrication methods. The thick film technique was proven as a promising and low cost fabrication method because of the controllable film thickness, thermal and electrical properties of thick-film substrate, integration of printed elements, and structure resolutions. These devices have high-power consumption and unsuitable sensing properties. Different metal oxides and noble metals were typically used to improve the sensing properties of sensors. The main goal of this study is to fabricate a gas sensor, based on mixed metal oxide material using thick film technology and improve the sensor sensitivity to carbon dioxide gas by adding of platinum (Pt). Choosing platinum between other noble metals such as Ag is because of its high thermal conductivity and non-corrosive property in faced with carbon dioxide gas. The process of fabrication consists of three main elements that include the heater,electrode, and a sensing layer which are printed over an alumina substrate. Pt paste was used for the heater and electrode layers, and La2O3/ SnO2 was utilized as a sensitive paste. Modification of sensing properties of the sensor and film morphology was carried out using Pt Nano-powder. The thermal treatment process was applied for all printed layers in order to dry the solvents and stabilize the sensitive layer over alumina substrate. Finally, sensitivity of the fabricated sensor was measured in presence of different carbon dioxide gas concentration. Crystalline size of sensitive material were analyzed by X-ray diffraction (XRD) analysis. The results showed that the particles size and phase shift of sensitive material were less than 30 nm and 20 nm, respectively. Sensing properties of all fabricated sensors were measured and compared to TGS 813 commercial gas sensor. The results showed that La2O3/ SnO2/ 3 wt. % Pt had better sensitivity up to 4.38 to carbon dioxide gas compared with sensitivity of 0.64, 0.32, and 0.005 for TGS 813, La2O3/ SnO2/ 1wt. % Pt and pure La2O3/ SnO2 gas sensors, respectively.